Retrospective Comparison of Minimally Invasive Plate Osteosynthesis and Open Reduction and Internal Fixation of Radius‐Ulna Fractures in Dogs. Issue 1 (26th November 2012) - Pozzi, Antonio; Hudson, Caleb C.; Gauthier, Christopher M.; Lewis, Daniel D.
<x xml:space="preserve">Abstract</x> Objective To compare the efficacy of reduction, time to union, and clinical outcome of radius and ulna fractures stabilized using either minimally invasive plate osteosynthesis (MIPO) or open reduction and internal fixation (ORIF). Study Design Retrospective, case‐controlled study. Animals Dogs with radius and ulna fractures stabilized with plates applied using MIPO (n = 15) or ORIF (n = 15). Methods Dogs in each stabilization group were matched for type and location of fracture, age, and body weight. Outcome measures including surgical time, fracture alignment, gap width, plate length, plate bridging and span ratio, working length and screw density, and time to union were compared between the groups using an unpaired t‐test. Statistical significance was set at P < .05. Results All fractures obtained radiographic union although infection developed in 1 dog in each stabilization group. Dogs treated with MIPO had a significant longer plate working length and lesser screw‐density (P < .05). No statistical difference was found in operating time, postoperative alignment, gap width, or time to union (MIPO: 51.9 ± 18.4 days; ORIF: 49.5 ± 26.5 days). Conclusions Radius and ulna fractures managed with MIPO had similar alignment, reduction, and time to union as fractures managed with ORIF. Future prospective clinical studies are warranted and should assess healing more frequently and in a standardized manner to compare MIPO to ORIF in a larger population of dogs.